2022
DOI: 10.1139/facets-2022-0148
|View full text |Cite
|
Sign up to set email alerts
|

Wastewater Surveillance for SARS-CoV-2 RNA in Canada

Abstract: Wastewater surveillance for SARS-CoV-2 RNA is a relatively recent adaptation of long-standing wastewater surveillance for infectious and other harmful agents. Individuals infected with COVID-19 were found to shed SARS-CoV-2 in their faeces. Researchers around the world confirmed that SARS-CoV-2 RNA fragments could be detected and quantified in community wastewater. Canadian academic researchers, largely as volunteer initiatives, reported proof-of-concept by April 2020. National collaboration was initially faci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 183 publications
0
10
0
Order By: Relevance
“…Wastewater surveillance (WS) has been an excellent alternative to monitor the scope of the COVID-19 pandemic in a community and is complementary to clinical testing for guiding public health measurements . Studies have shown that SARS-CoV-2 RNA in wastewater can appear 4–10 days prior to clinical PCR test results .…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Wastewater surveillance (WS) has been an excellent alternative to monitor the scope of the COVID-19 pandemic in a community and is complementary to clinical testing for guiding public health measurements . Studies have shown that SARS-CoV-2 RNA in wastewater can appear 4–10 days prior to clinical PCR test results .…”
Section: Introductionmentioning
confidence: 99%
“…Many countries have utilized metagenomic sequencing of SARS-CoV-2 RNA from wastewater samples to obtain high resolution sequence information and identify emerging and dominant variants in a specific community . Sequencing enables the identification of new and unique mutations that are used as targets in RT-qPCR to reveal information about the presence of specific variants. , With this sequencing information several variant-specific singleplex RT-qPCR assays have been developed and applied for the identification of Alpha, Beta, Gamma, or Delta in wastewater. ,, However, the RNA is present in wastewater at low concentration and fragmented, and consists of a mixture of SARS-CoV-2 variants, resulting in tremendous technical challenges with detection and reassembly of viral genomes from wastewater . Furthermore, sequencing approaches are time-consuming, expensive, and inaccessible in many countries with limited resources.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations